Pandangan Ahmadiyah Tentang Konsep “Khataman Nabiyyin” - Bimba Valid Fathony Bimba Valid Fathony (Canonia Religia, 2024)
The concept of prophethood in Islam is important because believing in prophets and messengers of God is one of the pillars of faith that Muslims must believe in. Ahmadiyah is an Islamic movement with a unique interpretation style, especially its concept of khātaman nabiyyīn. This research uses qualitative research methods with the type of library research. Ahmadiyya is divided into two groups, namely Qodian and Lahore. The Qodian group believes that Mirza Ghulam Ahmad is a Prophet, while the Lahore group only understands Mirza Ghulam Ahmad as a reformer. In general, Ahmadiyya has a concept of prophethood where there are prophets who bring Sharia and prophets who do not bring Sharia. Prophethood that does not bring new sharia has been possible throughout the ages. Ahmadiyya still believes that Prophet Muhammad was the last prophet who brought the Shari'ah. The word "khātam" has many meanings, including ring, seal, and seal. The phrase "khātamun nabiyyin" still hints that there is still an opening for prophethood that may open after the Prophet Muhammad.